The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1037/ppm0000400
|View full text |Cite
|
Sign up to set email alerts
|

Reactions to romantic relationship announcements in parasocial love and unrequited love.

Abstract: The present study examined people’s expected reactions to their beloved ones’ romantic relationship announcements in parasocial love (PSL) and unrequited love (UL). In a between-subjects design study, 330 college students in China were asked to name a media figure with whom they had PSL or someone they knew in person who had been their UL object. Then they reported their expected negative emotional reactions, closeness reduction, and coping strategies if the media figure or the love object announces romantic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 64 publications
(116 reference statements)
1
3
0
Order By: Relevance
“…These gender difference findings align with the gender differences reported in the above-mentioned PSR deterioration research (e.g., E. L. Cohen, 2010; Hu et al, 2021; Hu & Kong, 2022). Considering the accumulative evidence showing the differences between men and women, gender seems to be a factor that researchers must consider in future PSR deterioration research.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These gender difference findings align with the gender differences reported in the above-mentioned PSR deterioration research (e.g., E. L. Cohen, 2010; Hu et al, 2021; Hu & Kong, 2022). Considering the accumulative evidence showing the differences between men and women, gender seems to be a factor that researchers must consider in future PSR deterioration research.…”
Section: Discussionsupporting
confidence: 90%
“…Hu et al (2021) found that female fans expected greater closeness reduction and more negative reactions in response to their favorite media figures’ romantic relationship announcements. Hu and Kong (2022) discovered that, in both PSL and unrequited love, man and woman would-be lovers adopted different strategies to cope with romantic relationship announcements of their love objects.…”
Section: Psr Deteriorationmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this burgeoning addiction seeds a maelstrom of psychological turmoil and instabilities, posing an ominously detrimental threat to individual mental health as well as well-being (Fatah & Anindita, 2022;Duradoni et al, 2020). Furthermore, it engenders detrimental impacts on love relationships, contributing to the dissolution of love relationship closeness and satisfaction, thus tarnishing the joy and contentment of life (Hu & Kong, 2023;Roh, 2021;Steers et al, 2016;Veit et al, 2016).…”
Section: Research Background and Problem Statementmentioning
confidence: 99%